805 A Dangerous Wait: The Impact of Prolonged Waiting Times in Endocrine Surgery. (12th October 2021) - Shuttleworth, R; Eatock, F
Abstract: Aim: In Northern Ireland on 31/12/19 90, 514 patients were awaiting admission/day case procedure. The 2019/2020 Ministerial waiting time target states that by March 2020, 55% of patients should not wait longer than 13 weeks for inpatient/day case treatment, and no patient should wait longer than 52 weeks. This audit investigates the impact of long waiting times in endocrine surgery and how they impact patient safety. Method: Data was collected from the endocrine surgery waiting list in the Royal Victoria Hospital, Belfast, up to 6/2/20. Number of days spent on the waiting list, disease complications and the number of days before they occurred were collated. Results: 118 patients were awaiting endocrine surgery. The average waiting time was 533 days. 21 patients experience 27 complications related to their endocrine disease whilst waiting for surgery. The average duration before complications was 490 days; 4 required admission, 11 required medical intervention and 3 required a surgical intervention. Conclusions: The average waiting time for endocrine surgery is greater than 52 weeks. In Northern Ireland no one should be waiting more than 52 weeks. The length of the waiting list has resulted in 1 in 5 experiencing complications and prolonged suffering from under-treated disease. This is a significant patient safety concern. Urgent action to address waiting lists is required and the disruption caused by COVID-19 should be used as a catalyst for reform.